Tribocorrosion Behavior of Amorphous Carbon-Silicon Coated Titanium in Biological Medium (2018)
Studies of materials in biomedical applications have focused on the generation of new biomaterials and the development of surface modifications, mainly of metals. Amorphous silicon containing diamond like carbon DLC-Si coating deposited on titanium substrate with the purpose of studying its biofunctionality. The behavior against the phenomenon of tribocorrosion of coatings DLC-Si deposited on titanium was evaluated, through the plasma-assisted chemical vapor deposition technique. The nanoindentation technique was used to determine the coating mechanical properties. The DLC-Si coatings were structurally analyzed through X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) techniques, the characteristic binding energy for the signal C1s was obtained from XPS. Via XRD results the amorphous structure of DLC-Si coating was determined. The triboelectrochemical results indicate that the coating shows an adequate wear and to corrosion protection when exposed to the synergic mechanism, thus demonstrating the protective coating effect